Efficacy and Safety of Osteoporosis Medication in Renal Transplantation: A Systematic Review and Meta-Analysis - Sheikholeslami, Amir; Kharazmi, Amir Behnam; Sabaghian, Tahereh; Nasiri, Mohammad Javad (Novelty in Biomedicine, 2024)
Background: Osteoporosis is a significant concern, especially for individuals undergoing renal transplantation, as it disrupts bone health and increases the risk of fractures. Interventions for osteoporosis aim to address bone-related challenges in patients with renal transplantation, yet concerns persist regarding both efficacy and potential adverse events. Materials and Methods: We searched PubMed/MEDLINE, EMBASE, and the Cochrane CENTRAL databases until December 15, 2023, seeking studies that evaluated the efficacy and adverse events of osteoporosis medications in patients with renal transplantation. The Cochrane tool was utilized to assess the quality of the studies. The statistical analysis was performed using Comprehensive Meta-Analysis software, version 3.0. Results: We enrolled 594 participants from 7 randomized controlled trials. Combining trial results reveals that using anti-osteoporotic agents (Ibandronate, Risedronate, and Pamidronate) reduces the risk of vertebral fractures compared to the placebo. However, the reduction was not statistically significant (OR: 0.49, CI 95%: 0.20-1.22). Additionally, lumbar spine, femoral neck, and total hip BMD showed no significant differences between anti-osteoporotic agents (Denosumab, Zoledronic acid, Ibandronate, Risedronate, and Pamidronate) and placebo. Moreover, there were no significant differences in adverse events between the interventions and placebo. Conclusion: The study suggests that anti-osteoporotic agents in renal transplantation patients may be associated with a non-significant lower risk of vertebral fractures compared to a placebo. Findings also indicate no significant differences in adverse events between interventions and placebos. Caution is advised in interpreting these results due to the absence of statistically significant differences, emphasizing the need for further research to enhance our understanding of efficacy and safety in renal transplantation.